“They just left me”: people seeking asylum, mental and physical health, and structural violence in the UK’s institutional accommodation - Phillimore, Jenny; Fu, Lin; Jones, Lucy; Lessard-Phillips, Laurence; Tatem, Briony (Frontiers in Public Health, 2025)
This paper presents the findings of a novel post-hoc analysis of data collected by Doctors of the World UK (DOTW UK) between 2020 and 2022 from people seeking asylum housed in repurposed hotels and barracks in England. We analyzed qualitative and quantitative data on individuals’ mental and physical health using a structural violence analytical framework. Institutional housing and associated poor living conditions were reported to contribute deteriorations in physical and mental health which collectively undermined wellbeing. Inactions around urgent and life-threatening health conditions were seen as placing individuals’ lives and long-term health at risk. Provision of housing does not currently meet people’s needs and actively undermines their mental and physical health. We conclude that approaches to accommodation provision need to be adapted to ensure individuals’ right to health is realized. We outline recommendations for policy and future research.